Gap and Inequality in the Economic Income of Independent Workers in the Region of Puno-Peru and the Effect of the Pandemic, 2019–2020 - Julio C. Quispe Mamani; Giovana A. Flores Turpo; Dominga A. Calcina Álvarez; Cristóbal R. Yapuchura Saico; Wily L. Velásquez Velásquez; Santotomas L. Aguilar Pinto; Betsy Quispe Quispe; Nelly B. Quispe Maquera; Balbina E. Cutipa Quilca (Frontiers in Sociology, 2022)
ObjectiveThis article seeks to determine the social determinants of inequality in economic income in independent workers in the Puno region in the periods 2019 and 2020.MethodsFor which the quantitative approach was used, with descriptive and correlational design, considering the multiple regression model.ResultsIt was determined that there is a very significant income gap by educational level due to the productive differential that coronavirus disease 2019 (COVID-19) affected all the households; there is inequality in the economic income of independent workers, since in 2019, there was a greater inequality of economic income among independent workers (Gini = 0.6142) in relation to the national level (Gini = 0.415) and in 2020, the inequality of economic income increased due to COVID-19 problem, where the Gini coefficient amounted to 0.7136 in relation to the national level (Gini = 0.431).ConclusionThe determining factors of the economic income of the independent worker in the region of Puno in the periods 2019 and 2020 are the age that explains in 5.19 and 1.72%, the level of education that explains in 20.74 and 34.86% and the sex that explains in 37 and 14.19%, respectively.